Impact of Career Planning and Development as a HR Intervention to achieve Work Life Balance in Information Technology Industry - D.H. Malini, S. A. Senthil Kumar, M. Sampath Nagi, R. Renukadevi, (European Economic Letters (EEL), 2023)
Career planning is an important aspect for any employee and how far the organizations, are helping the employees in their career planning and development is utmost important. The career path is the backbone for any employee in Information Technology industry and choosing it is a very crucial task, because updating technical skills on a continuous basis is the lifeline to survive in this industry, and one who fails to do so, is out of this industry. One has to be multi-skilled to survive in this industry and one who depends upon just a particular technology/skill is considered to be outdated. Suggestion to the company are Exit interview feedback can be collected in HRIS, so the employees may give honest feedback. Same way one-on-one discussions should be conducted with the employees, in HRIS, to get honest feedback. These feedbacks, would help to bring out more employee-friendly, policies, which would bring more employee satisfaction and improves productivity. A satisfied employee would be able to manage his personal and professional life in a better way, there by achieving work life balance. However, a significant responsibility lies with the employees too in managing their personal and professional life. Proper planning in advance, between the work and family responsibilities, would help him/her a lot in avoiding work or family conflict and there by achieving work life balance.